Water‐Soluble Polymer Nanoparticles Constructed by Three‐Component Self‐Assembly: An Efficient Theranostic Agent for Phosphorescent Imaging and Photodynamic Therapy. Issue 15 (14th February 2017) - Yang, Qi; Shi, Min; Zhao, Heng; Lin, Jiaomin; An, Lu; Cui, Lili; Yang, Hong; Zhou, Zhiguo; Tian, Qiwei; Yang, Shiping
Abstract: Water‐soluble polymer nanoparticles NP‐1 and NP‐2 were prepared by using a three‐component self‐assembly of an iridium complex, poly(4‐vinyl pyridine‐b‐ethylene oxide) (P4VP‐b‐PEO), and methane sulfonic acid (MSA). Due to the unique metal‐ligand charge‐transfer transition property and the heavy‐atom effect of the iridium atom, NP‐1 and NP‐2 showed bright phosphorescence and generated the singlet oxygen ( 1 O2 ) species effectively under visible‐light irradiation ( λ >400 nm) with a power density of 300 mW cm −2 . NP‐2, an example of the polymer nanoparticles, showed minimal cytotoxic activity in the dark. Laser confocal fluorescence and flow‐cytometry microscopy experiments demonstrated that NP‐2 could be taken up by a model cancer‐cell line of 4T1 cells, which could be used as a phosphorescent probe for cell imaging by preferentially staining the cytoplasm. After 6 hours of incubation with NP‐2 (100 μg mL −1 ), the cell viability of 4T1 cells decreased to approximately 10 % upon visible‐light irradiation ( λ >400 nm, 300 mW cm −2 ) only for 10 minutes as a result of the generation of the 1 O2 species, thus indicating a proof of concept for effective photodynamic therapy for cancer cells. Abstract : Three's is the right number : Water‐soluble polymer nanoparticles were prepared by using a three‐component self‐assembly with an iridium complex, poly(4‐vinyl pyridine‐b‐ethylene oxide) (P4VP‐b‐PEO), and methane sulfonic acid (MSA). Metal‐ligand charge‐transfer transition and the heavy‐atom effect of iridium allow the nanoparticles to be used as single‐component theranostic agents for phosphorescent imaging and photodynamic therapy in vitro and under visible‐light irradiation (see figure).